Cell therapy for immunosuppression after kidney transplantation - Morath, Christian; Schmitt, Anita; Zeier, Martin; Schmitt, Michael; Şandra-Petrescu, Flavius Ionuţ; Opelz, Gerhard; Terness, Peter; Schaier, Matthias; Kleist, Christian (Langenbeck's archives of surgery, 2015)
To give an overview over cell therapeutic approaches to immunosuppression in clinical kidney transplantation. A focus is on myeloid suppressor cell therapy by mitomycin C-induced cells (MICs). Literature review with an emphasis on already existing therapies. Several cell therapeutic approaches to immunosuppression and donor-specific unresponsiveness are now being tested in early phase I and phase II trials in clinical kidney transplantation. Cell products such as regulatory T cells or regulatory macrophages, or other myeloid suppressor cell therapies, may either consist of donor-specific, third-party, or autologous cell preparations. Major problems are the identification of the suppressive cell populations and their expansion to have sufficient amount of cells to achieve donor unresponsiveness (e.g., with regulatory T cells). We show a simple and safe way to establish donor unresponsiveness in living-donor kidney transplantation by MIC therapy. A phase I clinical trial is now under way to test the safety and efficacy of this cell therapeutic approach. Cell therapeutic approaches to immunosuppression after kidney transplantation may revolutionize clinical transplantation in the future.